1970
DOI: 10.51703/bm.v2i2.9
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of tourist satisfaction among pull and push factors on tourists’ behavioural intentions; the study case of international tourists in Dili, Timor-Leste

Abstract: The objectives of this study are: (1) To identify and explain the push and pull factors which influence on tourists’ behavioural intention (2) To identify the influence of push and pull factors on tourist satisfaction; (3) To investigate and explain regarding role of tourist satisfaction as the mediation that will have an effect between push and pull factors on tourists’ behavioural intention. The findings show that push factors positively significant on tourists’ behavioural intention, but pull factors is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
0
4
0
3
Order By: Relevance
“…Dalam konteks pariwisata, tempat dan fasilitas wisata menjadi kunci penting untuk menarik wisatawan berkunjung ke suatu destinasi. Atraksi termasuk atraksi berwujud dan atraksi tak berwujud seperti pantai, pemandangan alam atau lanskap, dan lainlain (Baptista et al, 2020).…”
Section: Pull Factor (Faktor Penarik)unclassified
See 1 more Smart Citation
“…Dalam konteks pariwisata, tempat dan fasilitas wisata menjadi kunci penting untuk menarik wisatawan berkunjung ke suatu destinasi. Atraksi termasuk atraksi berwujud dan atraksi tak berwujud seperti pantai, pemandangan alam atau lanskap, dan lainlain (Baptista et al, 2020).…”
Section: Pull Factor (Faktor Penarik)unclassified
“…Dalam ajaran Islam, masjid sebagai tempat ibadah tidak hanya berarti bangunan atau tempat ibadah tertentu, karena dalam ajaran Islam, Allah SWT telah menjadikan seluruh alam semesta sebagai masjid ibadah. (Baptista et al, 2020).…”
Section: Masjidunclassified
“…Undeniably, the framework of push and pull theory has been widely used by researchers to examine issues in a variety of fields such as health and wellness (Ting et al, 2021), travel motivation (Luvsandavaajav, Narantuya, 2021), spa destinations (Dimitrovski, Seočanac, Lukovići, 2021), youth tourism (Preko, Doe, Dadzie, 2019) and events tourism (Qi, Smith, Yeoman, 2019). Therefore, the push-pull theory is popular among researchers as it is used extensively in the tourism field (Baniya, Ghimire, Phuyal, 2017;Baptista, Saldanha, Vong, 2020;Dimitrovski, Seočanac, Lukovići, 2021;Kim, 2021;Luvsandavaajav, Narantuya, 2021;Preko, Doe, Dadzie, 2019;Qi, Smith, Yeoman, 2019;Yousefi, Marzuki, 2015). These studies confirmed that the push and pull theory is applicable in the motives of tourists.…”
Section: Push and Pull Theorymentioning
confidence: 99%
“…Niezaprzeczalnie ramy teorii pushpull były szeroko stosowane przez naukowców do badania problemów z różnych dziedzin, takich jak: zdrowie i dobre samopoczucie (Ting i in., 2021), motywacja do podróży (Luvsandavaajav, Narantuya, 2021), miejsca uzdrowiskowe (Dimitrovski, Seočanac, Lukovići, 2021), turystyka młodzieżowa (Preko, Doe, Dadzie, 2019) oraz turystyka wydarzeń (Qi, Smith, Yeoman, 2019). Zatem teoria pushpull jest popularna wśród badaczy i szeroko stosowana w turyzmie (Baniya, Ghimire, Phuyal, 2017;Baptista, Saldanha, Vong, 2020;Dimitrovski, Seočanac, Lukovići, 2021;Kim, 2021;Luvsandavaajav, Narantuya, 2021;Preko, Doe, Dadzie, 2019;Qi, Smith, Yeoman, 2019;Yousefi, Marzuki, 2015). Badania te potwierdziły, że teoria pushpull ma zastosowanie do identyfikacji motywów kierujących turystami.…”
Section: Teoria Push-pullunclassified
“…Tourist intention has become an exciting topic of interest to many tourism scholars in recent years (Baptista et al, 2020). Various aspects contribute to understanding the behavioral intentions of tourists.…”
Section: Tourist Intentionmentioning
confidence: 99%